Architecture of vulnerability discovery technique for information systems - ZHANG You-chun1; WEI Qiang2; LIU Zeng-liang3; ZHOU Ying4 (Tongxin xuebao)
First,the definition of technical terms about vulnerability discovery were presented.The characters of the targets of vulnerability discovery were Analyzed.The general process of vulnerability discovery was studied.Then,by applying layer construction model way,proposed the architecture construction model of vulnerability discovery technique,which was divided into five layers,and also explained the contents,roles and key techniques of each layer.Finally,the future direction for the technique is that a comprehensive and coordinated method is used,with all the five layers taken into consideration.